2004
DOI: 10.4315/0362-028x-67.10.2288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postchill Application of Acidified Sodium Chlorite To Control Campylobacter spp. and Escherichia coli on Commercial Broiler Carcasses

Abstract: Experiments were performed to assess the reduction of Campylobacter spp. and Escherichia coli in commercial broiler carcasses by postchill dip applications of acidified sodium chlorite. Carcass rinses were collected before the inside-outside-bird washer (IOBW), post-IOBW, postchill, and after the postchill application of acidified sodium chlorite. Prevalence and counts of Campylobacter spp. and E. coli were determined. The mean values for Campylobacter spp. and E. coli counts differed significantly at sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…As another example, disease conditions within flocks (16) are reported to alter microbial numbers at the postchill stage. In addition, some slaughter plant interventions, such as carcass chilling, can result in differential reductions in Campylobacter and E. coli numbers (14). Cautious interpretation is therefore advised regarding relationships between E. coli levels and food-borne pathogens in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As another example, disease conditions within flocks (16) are reported to alter microbial numbers at the postchill stage. In addition, some slaughter plant interventions, such as carcass chilling, can result in differential reductions in Campylobacter and E. coli numbers (14). Cautious interpretation is therefore advised regarding relationships between E. coli levels and food-borne pathogens in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The committee acknowledged that, if valid, such a performance standard could facilitate inspection of slaughter processing establishments. The committee recommended studies to define how E. coli numbers vary in poultry carcass rinses during poultry processing by processing stage, time of year, and geographic region and with respect to foodborne pathogens.The widespread presence and high numbers of generic E. coli bacteria on poultry entering the slaughter establishment (2,5,14) are suitable characteristics for an indicator organism used to monitor microbial control processes. The ease and lower cost (5, 13) of E. coli enumeration also allow more observations than can be made when comparable resources are allocated for Campylobacter or Salmonella testing (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, European Community regulation 853/2004 permitted the use of substances other than water for decontamination of meat surfaces (3). Both physical and chemical reduction strategies, including treatment with steam, UV light, high hydrostatic pressure, essential oil fractions, acid, and sodium hypochlorite, have been investigated for their Campylobacter reduction potential, with various outcomes (1,9,10,13,16,24,28,33,35). DNA from dead bacterial cells has been shown to persist for up to 3 weeks following cell death (20), and it has also been demonstrated that the presence of DNA from dead Campylobacter cells can lead to an overestimation of the number of viable cells and, in some instances, even to false-positive results (45).…”
Section: Discussionmentioning
confidence: 99%
“…Oyarzabal et al (2004) and Sexton et al (2007), using that disinfectant in pre-chilling tanks also reported a reduction in Escherichia coli and Salmonella spp. counts in broiler carcasses.…”
Section: Evaluation Of Disinfectants Used In Pre-chilling Water Tanksmentioning
confidence: 91%